2021
DOI: 10.4103/ijciis.ijciis_8_20
|View full text |Cite
|
Sign up to set email alerts
|

Use of intensive care unit priority model in directing intensive care unit admission in Sudan

Abstract: Background: The shortage of specialized intensive care beds is one of the principal factors that limit intensive care unit (ICU) admissions. This study explores the utilization of priority criteria in directing ICU admission and predicting outcomes. Methods: This was a prospective cross-sectional study conducted in two ICUs in Sudan from April to December 2018. Patients were assessed for ICU admission and were ranked by priority into Groups 1, 2, 3, and 4 (1 highest pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Similarly, Caldeira et al and Abdalrahman et al declared that patients in priority categories of D and C had higher MR and longer ICU stay compared to groups A and B ( P < 0.05). They explained that the coexistence of several comorbidities among admitted patients in two mentioned categories in addition to having physical limitations or disabilities were also among key factors which were associated with substantially increases both hospital LOS and ICU mortality (Abdalrahman et al , 2021; Caldeira et al , 2013). Thus, appropriate use of ICU resources is of necessary significance due to inadequacy of beds worldwide.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, Caldeira et al and Abdalrahman et al declared that patients in priority categories of D and C had higher MR and longer ICU stay compared to groups A and B ( P < 0.05). They explained that the coexistence of several comorbidities among admitted patients in two mentioned categories in addition to having physical limitations or disabilities were also among key factors which were associated with substantially increases both hospital LOS and ICU mortality (Abdalrahman et al , 2021; Caldeira et al , 2013). Thus, appropriate use of ICU resources is of necessary significance due to inadequacy of beds worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the Multiple Organ Dysfunction Score evaluates organ dysfunction in patients continuously and is mentioned as an instrument for routine assessment of patient progress (Caldeira et al, 2013). In a prospective, cross-sectional study by Abdalrahman et al (2021), two main factors including age and comorbidity were mentioned as priority factors to allocate ICU beds. They found that older age and having many comorbidities were likely to be associated with priority 3 and 4, as related patients were more dependent, having longer stays in ICU and exhibiting higher MRs (Abdalrahman et al, 2021).…”
Section: Study Literaturementioning
confidence: 99%
See 2 more Smart Citations